2017
DOI: 10.4088/jcp.17f11629
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine for Depression, 2: Diagnostic and Contextual Indications

Abstract: There is a substantial body of literature comprising anecdotal material and descriptions of uncontrolled and randomized controlled trials addressing the use of subanesthetic doses of ketamine for the off-label treatment of major depressive episodes. This article examines diagnostic indications for the off-label use of ketamine as an antidepressant and possible contexts in which ketamine may be trialled. Ketamine is indicated in patients who are in a major depressive episode. Most of the research data have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…Therefore, if unanswered questions (Table 2) can be resolved in favor of ketamine, subanesthetic dosing with ketamine may become an important crisis intervention strategy to buy time while other treatments are instituted and take effect. 23 As discussed in earlier articles in this series, 1,2,4 respiratory risks with ketamine are low, even in anesthetic doses, and the drug is relatively safe, even in untrained hands, such as when used in military medical emergencies. An important possibility, then, is that ketamine may be a potential pharmacologic crisis intervention for the suicidal patient even in low-resource, primary care settings in developing countries, where facilities for psychiatric admission, psychotherapy, and ECT are unavailable.…”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if unanswered questions (Table 2) can be resolved in favor of ketamine, subanesthetic dosing with ketamine may become an important crisis intervention strategy to buy time while other treatments are instituted and take effect. 23 As discussed in earlier articles in this series, 1,2,4 respiratory risks with ketamine are low, even in anesthetic doses, and the drug is relatively safe, even in untrained hands, such as when used in military medical emergencies. An important possibility, then, is that ketamine may be a potential pharmacologic crisis intervention for the suicidal patient even in low-resource, primary care settings in developing countries, where facilities for psychiatric admission, psychotherapy, and ECT are unavailable.…”
Section: Commentsmentioning
confidence: 99%
“…P revious articles in this column discussed the efficacy, adverse effects, and possible mechanism(s) of action of subanesthetic doses of ketamine in the treatment of depression 1 ; the indications and contexts for the use of ketamine as an off-label antidepressant 2 ; the antidepressant benefits and adverse effects of ketamine and its enantiomers 3 ; issues related to dosing, rate of administration, route of administration, duration of treatment, and frequency of sessions when ketamine is used to treat depression 4 ; and potential pharmacokinetic and pharmacodynamic interactions when ketamine is used as an offlabel treatment for depression. 5 The present article examines the effects of ketamine on suicidal ideation and its possible use as a pharmacologic crisis intervention in patients at suicide risk.…”
Section: Department Of Psychopharmacology National Institute Of Mentmentioning
confidence: 99%
“…Yes, if the recent research on the antidepressant and antisuicidal action of ketamine is considered. There is a growing body of evidence that indicates that, in subanesthetic doses, ketamine has rapid antidepressant[ 14 15 16 17 18 ] and antisuicidal action. In fact, suicide risk is one context within a major depressive episode in which the use of ketamine has been specifically suggested.…”
Section: Ketamine As An Approach To the Management Of Suicide Riskmentioning
confidence: 99%
“…In fact, suicide risk is one context within a major depressive episode in which the use of ketamine has been specifically suggested. [ 15 ] Small studies conducted in emergency department settings have demonstrated that the antisuicidal effect of ketamine may even be apparent within 40 min of treatment. [ 19 20 ]…”
Section: Ketamine As An Approach To the Management Of Suicide Riskmentioning
confidence: 99%
“…Previous articles in this column considered issues related to the efficacy, adverse effects, and possible mechanism(s) of action of ketamine in the treatment of depression 1 ; discussed indications and contexts for the use of ketamine as an off-label antidepressant 2 ; evaluated the antidepressant benefits and risks of R-ketamine, S-ketamine, and racemic ketamine 3 ; and reviewed issues related to dosing, rate of administration, route of administration, duration of treatment, and frequency of sessions when ketamine is used in subanesthetic doses to treat depression. 4 The present article examines potential pharmacokinetic and pharmacodynamic interactions when ketamine is used as an off-label treatment for depression.…”
Section: Introductionmentioning
confidence: 99%